1. The problem statement, all variables and given/known data Use the Principle of Mathematical Induction and the Product Rule to prove the Power Rule when n is a positive integer. 2. Relevant equations Dxxn = nxn-1 Dx(fg) = fDxg + Dxfg 3. The attempt at a solution In summary, Dxxn = nxn-1 Dxxk = kxk-1 Dxxk+1 = (k+1)x(k+1)-1 Dx(xkx) = (k+1)xk xkDxx + Dxxkx = (k+1)xk xk + kxk-1x = (k+1)xk xk + kxk = (k+1)xk (k+1)xk = (k+1)xk Therefore, Dxxn = nxn-1 is valid for all positive integers n. EDIT: Oh, and much appreciation for any help!